2010
DOI: 10.3354/ab00272
|View full text |Cite
|
Sign up to set email alerts
|

Sound production by red hind Epinephelus guttatus in spatially segregated spawning aggregations

Abstract: Many fishes, including groupers, produce sounds associated with mating behavior; recording and analyzing the occurrence of these sounds can provide long time-series records of grouper use of spawning habitat. Red hind Epinephelus guttatus sound production was recorded on spawning aggregation sites off the west coast of Puerto Rico and at Mona Island, Puerto Rico. Audiovideo recordings were used to identify a species-specific sound produced by male red hind, most commonly during territorial patrols, and also du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 11 publications
3
71
0
Order By: Relevance
“…Daily sound levels show trends similar to the density build-up and post-spawning departure described by Nemeth et al (2007), with maximum levels around sunset (Mann et al 2010) when red hind have been observed spawning (Colin et al 1987). While passive acoustic methods have been used to describe patterns of sound production at red hind spawning aggregations, the relationship between changes in red hind sound production and density has not been established.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Daily sound levels show trends similar to the density build-up and post-spawning departure described by Nemeth et al (2007), with maximum levels around sunset (Mann et al 2010) when red hind have been observed spawning (Colin et al 1987). While passive acoustic methods have been used to describe patterns of sound production at red hind spawning aggregations, the relationship between changes in red hind sound production and density has not been established.…”
Section: Introductionmentioning
confidence: 61%
“…Red hind produce a low frequency mixed tonalpulse species-specific vocalization associated with courtship and territorial behaviors at spawning aggregations , Mann et al 2010. Daily sound levels show trends similar to the density build-up and post-spawning departure described by Nemeth et al (2007), with maximum levels around sunset (Mann et al 2010) when red hind have been observed spawning (Colin et al 1987).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations